2018
DOI: 10.1002/ejoc.201701749
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Photo‐Caged DOPA Derivative by Selective Alkylation of 3,4‐Dihydroxybenzaldehyde

Abstract: Natural and synthetic polymers containing the catechol moiety of noncoded amino acid 3,4‐dihydroxyphenylalanine (DOPA) are capable of metal‐coordination and adhesion under wet conditions. Masking the catechol subunit with a photo‐cleavable group would provide an opportunity to design tunable adhesion properties that are especially important for biomaterial and biomedicine applications. Herein, we report the regioselective synthesis of a photo‐caged DOPA bearing an ortho‐nitrobenzyl (oNB) group that is capable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Owing to these properties, the authors suggested that this adhesive material is well suited for the repair of tendon-to-bone injuries. Taking advantage of the genetic code expansion technology can not only high efficiently introduce Dopa functionality but also engineer UV-responsive smart adhesives by incorporating photocaged Dopa derivatives ( Hauf et al, 2017 ; Schneider et al, 2017 ; Schneider et al, 2018 ).…”
Section: Barnacle Cement–inspired Adhesive Materialsmentioning
confidence: 99%
“…Owing to these properties, the authors suggested that this adhesive material is well suited for the repair of tendon-to-bone injuries. Taking advantage of the genetic code expansion technology can not only high efficiently introduce Dopa functionality but also engineer UV-responsive smart adhesives by incorporating photocaged Dopa derivatives ( Hauf et al, 2017 ; Schneider et al, 2017 ; Schneider et al, 2018 ).…”
Section: Barnacle Cement–inspired Adhesive Materialsmentioning
confidence: 99%
“…Characterization data were in agreement with previously reported values. 29 (4-((tert-Butyldimethylsilyl)oxy)-3-methoxyphenyl)methanol (S25). To a solution of aldehyde S24 (1.96 g, 7.5 mmol) in MeOH (23 mL) was added NaBH 4 (318 mg, 9.0 mmol) at 0 °C.…”
Section: -(((3-hydroxybenzyl)oxy)methyl)-2-methoxyphenol (1l)mentioning
confidence: 99%
“…Characterization data were in agreement with previously reported values. 29 (4-(Bromomethyl)-2-methoxyphenoxy)(tert-butyl)dimethylsilane (S26). To a solution of alcohol S25 (1.07 g, 4.0 mmol) in CH 2 Cl 2 (12 mL) was added PBr 3 (0.30 mL, 3.2 mmol) slowly at 0 °C.…”
Section: -(((3-hydroxybenzyl)oxy)methyl)-2-methoxyphenol (1l)mentioning
confidence: 99%
See 1 more Smart Citation
“…15 A combination of methods b and c , referred as the Bucherer–Bergs reaction, also furnishes 5,5-disubstituted hydantoins. 16 In contrast, our synthetic method (method d ) achieved the synthesis of amino acid derivatives by decarboxylation 17 of α,α-disubstituted malonate, in which the α-substituent is easily modified by altering the nucleophile. Because α,α-disubstituted malonate has multiple coordination sites, control of stereochemistry is expected to be easier than methods a–c .…”
Section: Introductionmentioning
confidence: 99%